An update on the distribution of the genus Trachelas L. Koch, 1872 (Araneae, Trachelidae) in China, with description of a new species - Liu, Kaizhen; Liu, Jiannan; Zhang, Feng; Li, Liangtao; Mi, Xiaoqi; Jin, Chi (Zootaxa, 2024)
The distribution of the genus Trachelas L. Koch, 1872 in China is updated by reviewing literature and examining specimens. One new species, T. bomiensis Jin & Mi, sp. nov. (♂♀), is described from the Xizang Autonomous Region, China.